Acting for health: Effective actor preparation for health-care simulations. Issue 3 (1st September 2015) - Loth, Jo; Andersen, Patrea; Mitchell, Patrick
This article provides a summary of the current literature (1975–2015) on the subject of effective 'simulated patient' training, with a focus on developing best practice for actor preparation for simulated patient work. There has been a great deal written about the efficacy of simulation in health care, and the importance of training for actors in simulation learning is acknowledged by a range of academics. This article discusses the theatrical and performative contexts of simulated patients and the training needs for actors. It concludes that actors must be acutely aware of the educational needs of the students, and the importance of maintaining a controlled and equitable learning environment. Understandings from this literature review are currently informing the project Acting 4 Health, in which drama students are trained as simulated patients for learning events in nursing at the University of the Sunshine Coast.